Clinical significance of the presence of puff‐chandelier ruptures detected by nonobstructive aortic angioscopy. Issue 4 (9th November 2019) - Yamaguchi, Masao; Yonetsu, Taishi; Hoshino, Masahiro; Sugiyama, Tomoyo; Kanaji, Yoshihisa; Ohya, Hiroaki; Hada, Masahiro; Sumino, Yohei; Kanno, Yoshinori; Hirano, Hidenori; Yuki, Haruhito; Horie, Tomoki; et al.
Abstract: Objective: This study aimed to investigate the prevalence and prognostic significance of atherosclerotic aortic plaques (AAPs) or specific AAP types detected by nonobstructive angioscopy (NOA) in patients who underwent percutaneous coronary intervention (PCI). Background: Although recent studies have reported the presence of various patterns of AAPs, identified by NOA, the clinical significance of the presence of AAPs remains elusive. Methods: In this retrospective, multicenter cohort study, a total of 167 patients who underwent PCI and intra‐aortic scans with NOA were studied. The association between AAPs and the incidence of major adverse cardiac events (MACEs), including cardiac death, myocardial infarction, stroke, and clinically driven unplanned revascularizations, was assessed. Results: AAPs were detected in 126 patients (75%) who underwent NOA. MACEs occurred in 28 (17%) patients during the follow‐up (median 2.9 years [range 2.1–3.8]). Among all types of AAPs, only puff‐chandelier rupture (PCR) showed a significant difference in frequency between patients with and those without MACEs: 21 (75%) and 49 (35%), respectively ( p  < .001). Multivariable Cox proportional hazard analysis revealed that PCR (hazard ratio [HR] 3.73, 95% confidence interval [CI] 1.57–8.87, p = .004) and chronic kidney disease (HR 2.97, 95% CI 1.37–6.44, p = .010) were independent predictors of MACEs. Kaplan–Meier analysis revealed that PCR was significantly associated with more frequent MACEs. Conclusion: The detection of PCR in the aorta using NOA was significantly associated with an increased risk of subsequent adverse events after PCI.